REQUEST FOR PROTECTION OF LEGALITY - Bugarski, Tatjana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2016)
The author of this work, attention to the request for protection of legality as an extraordinary legal remedy which has significantly modified the latest Code of Criminal Procedure (2011). This extraordinary remedy is an instrument that ensures the rule of law in criminal proceedings and the dam is a kind of legality and constitutionality of the actions and decisions of the judicial authorities. As an important mechanism to elimination of illegality in criminal proceedings, including the illegality in connection with the execution of evidentiary actions, the author's attention to the analysis of positive solutions in our criminal procedural legislation in connection with a request for protection of legality and compared with certain comparative solutions. Special attention is devoted to certain contentious issues regarding this extraordinary remedy, and jurisprudence.